Financial toxicity: a potential side effect of prostate cancer treatment among Australian men. (1st October 2015) - Gordon, L.G.; Walker, S.M.; Mervin, M.C.; Lowe, A.; Smith, D.P.; Gardiner, R.A.; Chambers, S.K.
Abstract : The purpose of this study was to understand the extent, nature and variability of the current economic burden of prostate cancer among Australian men. An online cross‐sectional survey was developed that combined pre‐existing economic measures and new questions. With few exceptions, the online survey was viable and acceptable to participants. The main outcomes were self‐reported out‐of‐pocket costs of prostate cancer diagnosis and treatment, changes in employment status and household finances. Men were recruited from prostate cancer support groups throughout Australia. Descriptive statistical analyses were undertaken. A total of 289 men responded to the survey during April and June 2013. Our study found that men recently diagnosed (within 16 months of the survey) ( n  = 65) reported spending a median AU$8000 (interquartile range AU$14 000) for their cancer treatment while 75% of men spent up to AU$17 000 (2012). Twenty per cent of all men found the cost of treating their prostate cancer caused them 'a great deal' of distress. The findings suggest a large variability in medical costs for prostate cancer treatment with 5% of men spending $250 or less in out‐of‐pocket expenses and some men facing very high costs. On average, respondents in paid employment at diagnosis stated that they had retired 4–5 years earlier than planned.